1917 Utah Laws 278, ch. 95, § 1 - (:unkn) unknown (My University, 1917)
Prohibited noncitizens from owning, possessing, or having under their control and shot gun, rifle or firearm " of any make. "
Keywords: POSSESSION - DANGEROUS PERSONS